2015
DOI: 10.5901/mjss.2015.v6n4s4p118
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Governance: Mechanisms for Control and Alignment of Interests of Participants of Corporate Relations in the Transitive Economy

Abstract: The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
1
0
Order By: Relevance
“…(Rahman & Bremer, 2016) examining a sample of 452 listed industrial corporations in the US measuring their Tobin's Q with respect to board size from 1984 till 1991, and proves that there is a significant inverse relation between board size and firm performance. Moreover, in the same study, (Tarando et al, 2015) finds that smaller board companies have improved values for financial ratios. A sample of 164 companies listed on Bombay Stock Exchange (BSE) was studied for six financial years from 1998 till 2003 by Garg in 2007, while taking into account Tobin's Q and other market ratios, and discovered a negative association between board size and firm performance, and also recommended that the optimal board size must be limited to six (6) members.…”
Section: Number Of Directors At the Level Of The Boardmentioning
confidence: 77%
“…(Rahman & Bremer, 2016) examining a sample of 452 listed industrial corporations in the US measuring their Tobin's Q with respect to board size from 1984 till 1991, and proves that there is a significant inverse relation between board size and firm performance. Moreover, in the same study, (Tarando et al, 2015) finds that smaller board companies have improved values for financial ratios. A sample of 164 companies listed on Bombay Stock Exchange (BSE) was studied for six financial years from 1998 till 2003 by Garg in 2007, while taking into account Tobin's Q and other market ratios, and discovered a negative association between board size and firm performance, and also recommended that the optimal board size must be limited to six (6) members.…”
Section: Number Of Directors At the Level Of The Boardmentioning
confidence: 77%
“…The main part of researches focus on the results of the administrative reforms in different countries and in different terms. They analyse the problems of the efficiency of the system of public goods (Banerjee and Hankla, 2014;Kumar, 2014;Puron-Cid, 2014;Knox, 2008;Héritier, 2001;Tarando et al, 2015) of the concept of 'good government' or 'performance management' as the next stage of reform (West and Blackman, 2015;Ullah, 2014) or of the professionalising of civil service during the reform (Gellén, 2013;O'Flynn et al, 2011;Volchkova and Pavenkova, 2002). They found that public service needs further transparency and strengthening of cooperation with civil society.…”
Section: Introductionmentioning
confidence: 99%